Detection of Pseudomonas pseudomallei by PCR and hybridization. - Lew, A E (1994)
A molecular method for the detection of Pseudomonas pseudomallei was developed on the basis of the differences in the 23S rRNA sequences of related species of the genus Pseudomonas. An 18-base oligonucleotide probe, designed following partial sequencing of 23s ribosomal DNA (rDNA), was used for the identification and detection of P. pseudomallei either by hybridization or by direct PCR. Optimal detection was obtained by hybridization of the probe with PCR-amplified rDNA rather than with total genomic DNA or colony blots. One nanogram of template DNA amplified in a PCR mixture containing 14% glycerol could be detected in slot blots hybridized with the digoxigenin-labelled probe and the lumigen PPD detection system. Amplified rDNA sequences from 41 P. pseudomallei strains of various origins hybridized with the probe. The probe also hybridized with three Pseudomonas mallei reference strains under conditions of high stringency but failed to hybridize with amplified rDNA sequences from other closely related Pseudomonas spp. PCR with a conserved primer and the 18-base oligonucleotide probe (direct PCR) specifically amplified P. pseudomallei and P. mallei. By using these methods, approximately 10(4) P. pseudomallei cells per ml could be detected in artificially inoculated blood samples and in blood dried on filter paper following Chelex extraction. The detection limit in blood was increased to 10(2) cells per ml by concentration of bacteria from 0.5 ml of blood or by a 24-h blood culture enrichment prior to PCR. Approximately 10(3) cells per ml were detected in seeded sputum samples. The detection times by direct PCR and indirect PCR and then probe hybridization were approximately 5 h and 24 h, respectively. These results indicate that amplification of conserved rDNA sequences by PCR directly or by hybridization with a probe to PCR fragments offers promise for the detection of P. pseudomallei and P. mallei.